Clinical study on localization of calcific tendinitis of the supraspinatus tendon based on three-dimensional reconstruction technology of CT scan - Jia, Shicheng; Liu, Xiaolei; Li, Menghao; Mu, Xin; Lin, Jianjing; Chen, Jiayou; Lu, Shengbo; Li, Wei (Frontiers in Surgery, 2025)
BackgroundArthroscopic resection of calcific lesions is an effective treatment for calcific tendonitis. However, accurately locating the calcific foci can be challenging. In this study, we propose the use of preoperative 3D-CT scan technology combined with intraoperative patient position and markings to precisely locate intraoperative lesions. The aim is to reduce exploration time and operative time.MethodsWe retrospectively analyzed 51 cases of calcific tendonitis from inpatients at our department from June 2016 to January 2024. The patients were divided into a localization group (n = 26) and a non-localization group (n = 25) based on whether preoperative 3D-CT scan and intraoperative patient markings were used for lesion localization. In the localization group, the calcific lesions were located on the skin surface using the improved preoperative 3D-CT scan and intraoperative patient markings technique. In the non-localized group, a conventional surgical approach was performed. The intraoperative exploration time and operation time were compared between the two groups. ASES scores, VAS scores, and shoulder mobility were recorded before the operation, after the operation, and at the one-month postoperative follow-up.ResultsThe localization group had significantly shorter intraoperative exploration time and operation time compared to the non-localization group (p < 0.01). There were no significant differences in ASES scores, VAS scores, and shoulder mobility between the two groups (p > 0.05).ConclusionThe improved preoperative 3D-CT scan and intraoperative patient markings technique is a simple and effective method for localizing calcific tendonitis lesions before arthroscopic exploration. This technique can reduce exploration time and shorten operative time.Level of evidenceLevel III; Cohort Study; Retrospective Study.